VARIABLE GENETIC EXPRESSIONS AND INTERRELATIONSHIP BETWEEN GRAIN YIELD AND SOME QUALITY TRAITS OF ACHA (Digitaria spp.) ACCESSIONS IN JOS PLATEAU (FULafia Journal of Science and Technology, 2023)
Acha (Digitaria exillis kippis. Stapf and D. iburua Stapf L) is one of the oldest West African cereal and of great value to the natives. It belongs to the Poaceae (Grass) family. Despite its potentials, Acha has remained a marginal crop. The present study focused on the evaluation of the variable genetic expressions and interrelationship between grain yield and some morphological traits of some Acha accessions. These accessions were collected from farmers in five villages of Bokkos Local Government Area of Plateau State. This work was conducted at the end of the 2019 rainy season at the Federal College of Forestry Jos. Grains were harvested from the experimental field and proximate analysis was conducted for the Ash content, crude fat, crude fibre, protein content, carbohydrate content, moisture content, dry matter content and energy values. Analysis of variance revealed variability among the different accessions and the variability spanned the nutritional composition of Acha.
Keywords: Digitaria spp.; Acha; Proximate Analysis; Genotypic and Phenotypic Variance; Genotypic and Phenotypic Coefficient of Variance